Evaluating brain modularity benefits of an acting intervention: a discriminant-analysis framework - Rajesh, Aishwarya; Betzel, Richard; Daugherty, Ana M.; Noice, Tony; Noice, Helga; Baniqued, Pauline L.; Voss, Michelle W.; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2023)
Purpose: Aging is associated with a reduction in brain modularity as well as aspects of executive function, namely, updating, shifting, and inhibition. Previous research has suggested that the aging brain exhibits plasticity. Further, it has been hypothesized that broad-based intervention models may be more effective in eliciting overall gains in executive function than interventions targeted at specific executive skills (e.g., computer-based training). To this end, we designed a 4-week theater-based acting intervention in older adults within an RCT framework. We hypothesized that older adults would show improvements in brain modularity and aspects of executive function, ascribed to the acting intervention. Materials and Methods: The participants were 179 adults from the community, aged 60–89 years and on average, college educated. They completed a battery of executive function tasks and resting state functional MRI scans to measure brain network modularity pre- and post-intervention. Participants in the active intervention group (n=93) enacted scenes with a partner that involved executive function, whereas the active control group (n=86) learned about the history and styles of acting. Both groups met two times/week for 75-minutes for four weeks. A mixed model was used to evaluate intervention effects related to brain modularity. Discriminant-analysis was used to determine the role of seven executive functioning tasks in discriminating the two groups. These tasks indexed subdomains of updating, switching, and inhibition. Discriminant tasks were subject to a logistic regression analysis to determine how post-intervention executive function performance interacted with changes in modularity to predict group membership. Results: We noted an increase in brain modularity in the acting group, relative to pre-intervention and controls. Performance on updating tasks were representative of the intervention group. However, post-intervention performance on updating did not interact with the observed increase in brain modularity to distinguish groups. Conclusion: An acting intervention can facilitate improvements in modularity and updating, both of which are sensitive to aging and may confer benefits to daily functioning and the ability to learn.